PARAGRAPH DEVELOPMENT BY APPLYING LEARNING EXPERIENCE APPROACH TO ENHENCE STUDENT’S WRITING ABILITY - Nila Kencana; Melati Melati (English Education Study Program Faculty of Teacher Training and Education, 2020)
The objective of the research was to find out and describe the improvement in writing skills through the Experience-based Learning Approach. The method of this research was classroom action research which was conducted in two cycles. The subject of this research was students of the 4th semester of English Education Study Program Faculty of Teacher Training and Education of UNIHAZ 2016/2017. The research instruments were the observation sheet, interview guidelines, questionnaire and test form. Based on the results of data analysis of pre-test and post-test shown the significant improvement. The student average increased by 13.7 points with an increase of 20%. Meanwhile, from cycle I to cycle II, the average writing ability of students increased by 2.4 points with a percentage increase of 80%. Based on the learning activities which have occurred the enhancing from the first to second cycles from this research findings, it showed that LEA could improve the students’ writing ability.